Functional Biodegradable Nanocomposites - López, Daniel; Echeverría, Coro; Sonseca, Águeda (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Concern around environmental issues facing society has grown significantly in recent years. Reduction in damages resulting from both industrial and domestic waste has become a key topic as a means to address environmental problems and the exhaustion of natural resources. Likewise, the use of materials of polymeric origin in applications such as tissue regeneration, controlled release of medicines, packaging, soil remediation, etc., makes the development of materials biodegradable in biological media increasingly important. Recently, significant progress has been achieved in the creation of biodegradable polymeric formulations with functionalities similar to those of non-biodegradable polymers, both of natural and of synthetic origin, extending their applicability to fields such as food packaging, electronics, production of health-related materials, agriculture, etc. In this context, biodegradable nanocomposites offer new and exciting possibilities. This book deals with the development of functional polymer nanocomposites that can undergo biodegradation in different media, including biological systems, soils, landfills, etc. Original and review articles covering aspects of polymer science and technology, such as synthesis, processing, characterization, properties, and applications of functional biodegradable nanocomposites for different applications, are included in this book.